Pengaruh Metode Learning Contract terhadap Hasil Belajar Sejarah Indonesia Kelas X IPS - Nahdatul Hazmi; Fikrul Hanif Sufyan; Yuhasnil Yuhasnil (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the effect of the application of the learning contract method on learning outcomes of Indonesian history. This research method is quasi-experimental research. The population in this study were all students of class X IPS with a total of 86 students. The sampling technique is cluster sampling. The results of the study conducted t-test. Based on the results of the sample class normality test, the sample class has L0 0.00706 < Lt 0.173 with a significant level (Î±=0.05), which means that the sample classes are normally distributed. To find out whether the two groups of data have a homogeneous variant or not, an F test is carried out, so the sample class has Fcount 1.16 < Ftable 1.88, meaning that the two sample classes have homogeneous variants. The results of the hypothesis test obtained tcount: 3.91 while ttable at a significant level (Î± = 0.05) is 1.68 meaning tcount > ttable so that H1 is accepted, and Ho is rejected. The conclusion of this study is that there is a positive effect of the application of the learning contract method on the results of learning Indonesian history in class X IPS at SMAN 1 Lareh Sago Halaban which makes students active in learning so that the learning process becomes more meaningful. Keywords: Learning Contract, Learning Outcomes